A Production and operations management study on Universal Stainless Ware Manufacturing Company, Inc. - Cajustin, Jason J. (College of Engineering, 1999)
A Productions and Operations Management study was conducted on one of the plants of Universal Stainless Ware Manufacturing Company, Inc. which manufactures sauce pots and chafing dishes. The study included documentation, evaluation, and analyses of the facility's present production system, facility layout, forecasting, strategic capacity planning, aggregate planning, ad identification of possible improvement areas along with their corresponding recommendations. The processes for both body and cover parts of saucepots and chafing dishes were documented. All documentation of company systems was analyzed for the purpose of the evaluation. Forecasting the demand for their products was facilitated through the decomposition of a time series technique, and evaluated through its tracking signal. The monthly forecasts for the years 2001 and 2002 were used as the basis for planning future capacities and workforce level requirements. Analyses of the current system resulted in the identification of the following problem areas: (1) Bottlenecks; (2) Under-utilization of machines; and (3) No forecasting technique. To address the problem areas, the implementation of the following recommendations were presented: (1) Apply aggregate planning; (2) Add more workers; (3) Use improved layout; and (4) Apply appropriate forecasting method. In applying aggregate planning, three alternative strategies were considered by the group, the chase strategy, level strategy, and mixed strategy. The mixed strategy proves to be the best alternative considering both quantitative factors, such as total costs and qualitative factors, like morale od workers and inventory level. This strategy suggests that the company maintains 45 workers during the peak months, 30 workers during the lean month, and 35 workers for the remaining months. For the bottleneck problem, the group suggests that two more workers should be added to the limiting process, which is spot welding. This would increase the efficiency of the layout by 8%. in applying appropriate forecasting technique, the group used the Decomposition of a Time Series Technique to obtain the demand forecast. With this method, the seasonality and trend effects of the demand have been considered. Applying this forecasting technique, the company would be able to increase their productivity, estimate the workforce level per month, determine the schedule for ordering their raw materials and significantly decrease inventory level.